Potato ingestion is as effective as carbohydrate gels to support prolonged cycling performance - Salvador, A. F.; McKenna, C. F.; Alamilla, R. A.; Cloud, R. M. T.; Keeble, A. R.; Miltko, A.; Scaroni, S. E.; Beals, J. W.; Ulanov, A. V.; Dilger, R. N.; Bauer, L. L.; Broad, E. M.; et al. (Journal of Applied Physiology, 2019)
Carbohydrate (CHO) ingestion is an established strategy to improve endurance performance.Race fuels should not only sustain performance but also be readily digested and absorbed. Potatoes are a whole-food-based option that fulfills these criteria, yet their impact on performance remains unexamined. We investigated the effects of potato purée ingestion during prolonged cycling on subsequent performance vs. commercial CHO gel or a water-only condition. Twelve cyclists (70.7 7.7 kg, 173 8 cm, 31 9 yr, 22 5.1% body fat;means SD) with average peak oxygen consumption (VO2peak) of 60.7+/- 9.0 mL·kg -1·min-1 performed a 2-h cycling challenge (60-85% VO2peak) followed by a time trial (TT; 6 kJ/kg body mass) while consuming potato, gel, or water in a randomized-crossover design. The race fuels were administered with [U-13C6]glucose for an indirect estimate of gastric emptying rate. Blood samples were collected throughout the trials. Blood glucose concentrations were higher (P< 0.001) in potato and gel conditions compared with water condition.Blood lactate concentrations were higher (P= 0.001) after the TT completion in both CHO conditions compared with water condition. TT performance was improved (P= 0.032) in both potato (33.0+/-4.5min) and gel (33.0+/- 4.2 min) conditions compared with wate rcondition (39.5 +/-7.9 min). Moreover, no difference was observed in TT performance between CHO conditions (P= 1.00). In conclusion,potato and gel ingestion equally sustained blood glucose concentrations and TT performance. Our results support the effective use of potatoes to support race performance for trained cyclists.